Déterminants Et Contraintes De La Pratique De L’apiculture Dans Les Communes De Djidja Et Zogbodomey Au Sud Du Bénin (Afrique De l’Ouest) - Paraïso, Grégoire; Adjoha, Bienvenu; Paraïso, Armand; Ayélerou, Roméo; Orou-Goura, Zackari (European Scientific Journal, ESJ, 2017)
Beekeeping is a very interesting activity having a positive impact on agricultural production and rural incomes. This study conducted in both municipalities of Djidja and Zogbodomey, in southern Benin, aimed at analyzing the determinants and constraints of beekeeping activities. For this purpose, a sample of 110 beekeepers randomly selected was investigated. Data about socio-economic and demographic characteristics of households as well as the difficulties in beekeeping were collected through individual interviews and focus groups. The statistical analysis done with R software version 3.1.2 have shown that beekeeping in the study area was influenced by three important socio-economic factors such asthe municipality of the producer, , literacy level and the producer belonging to a village agricultural association. The studies also revealed that the development of beekeeping faced many problems such as: the lack of financial resources, the low level of knowledge in beekeeping techniques, the lack of extension services, the high level of parasitism and other forms of constraints as theft, bush fire. Taking into account these results will allow to pay more attention on farmers’ and beekeepers situation what will be a means of alleviating of rural poverty.